TI_GERICHTE 60.2007.358 vom 14. November 2007 , Istanza di ricusa nei confronti del presidente della Camera dei ricorsi penali - TI Tribunale d'appello (2007)
Istanza di ricusa nei confronti del presidente della Camera dei ricorsi penali